2016
DOI: 10.1155/2016/4694367
|View full text |Cite
|
Sign up to set email alerts
|

Screening Antimicrobial Activity of Nickel Nanoparticles Synthesized Using Ocimum sanctum Leaf Extract

Abstract: Antimicrobial efficacy of nickel nanoparticles synthesized using leaf extract of Ocimum sanctum (NiGs) was investigated against pathogenic Gram-negative (E. coli, K. pneumoniae, and S. typhi), Gram-positive (B. subtilis, S. epidermidis) bacteria and fungi (C. albicans, C. tropicalis, A. fumigatus, A. clavatus, and A. niger). 100 µg/mL NiGs showed maximum antimicrobial activity against tested pathogens compared to leaf extract and antibiotics. E. coli (25 mm) and C. albicans (23 mm) exhibited higher zone of inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Physically, nano‐Ni can damage skin, tissue/organ surfaces, cell walls, and internal membranes, presumably through production of ROS that disrupts structural integrity (Gallo et al 2016; Oukarroum et al 2017; Peng et al 2018) and leads to leakage of intracellular proteins across membranes into the extracellular medium (Jeyaraj Pandian et al 2016). Exposure to nano‐Ni can also lead to cell enlargement and aberrant cell morphology (Oukarroum et al 2017; Sousa et al 2018b), and it has even been reported to cause skeletal damage such as scoliosis in fish (Morgaleva et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physically, nano‐Ni can damage skin, tissue/organ surfaces, cell walls, and internal membranes, presumably through production of ROS that disrupts structural integrity (Gallo et al 2016; Oukarroum et al 2017; Peng et al 2018) and leads to leakage of intracellular proteins across membranes into the extracellular medium (Jeyaraj Pandian et al 2016). Exposure to nano‐Ni can also lead to cell enlargement and aberrant cell morphology (Oukarroum et al 2017; Sousa et al 2018b), and it has even been reported to cause skeletal damage such as scoliosis in fish (Morgaleva et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, nano‐Ni can cause chemical damage. Nano‐Ni induces production or release of ROS inside of or external to organisms (Han et al 2012; Zhang et al 2013; Fu et al 2014; Oukarroum et al 2015, 2017; Jeyaraj Pandian et al 2016; Peng et al 2018; Sousa et al 2018a, 2018b, 2018c). This is a common mechanism of many metal‐containing NPs, leading to oxidative stress (Canesi et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account all these points, the most probable clinical use against bacterial infections of metal NPs would be restricted to topical or local use. Over the last few years, other element such as, nickel [ 165 , 166 ], cerium [ 166 , 167 ], Se [ 168 , 169 ], caesium [ 170 ], yttrium [ 171 ], palladium [ 172 , 173 ], or superparamagnetic Fe NPs [ 174 ] have been recently employed in the battle against antibiotic-resistant bacteria [ 21 , 125 ], but more studies that include cytotoxicity and biocompatibility are necessary.…”
Section: Nanoparticles and Human Infectionsmentioning
confidence: 99%
“…Similarly, NiO nanoparticles biosynthesized from fresh leaves of the Neem plant have shown bacterial cell membrane disruption, which resulted in the death of bacterial cells (Helan et al, 2016). Moreover, the inhibition efficiency of bacterial growth was enhanced in the presence of amoxicillin together with Ni nanoparticles (Jeyaraj Pandian et al, 2016).…”
Section: Introductionmentioning
confidence: 99%